2005
DOI: 10.1039/b508214e
|View full text |Cite
|
Sign up to set email alerts
|

Acid-catalysed formation of tricyclic N,S-acetals in imidazolinone series based on the use of the unprecedented N-acyliminium ion cascade reaction involving transposition, heterocyclisation and π-cyclisation

Abstract: 4-Hydroxy-5,5-dimethylimidazolines tethered at N-1 to an aryl sulfide undergo an unprecedented acid-catalysed domino reaction, involving double methyl transposition, heterocyclisation, isomerisation of thiazetidinium ion and, finally, pi-cyclisation. In this way a one-pot synthesis of original tricyclic N,S-acetals was developed. The same triheterocyclic products can be prepared also starting from the corresponding 5-hydroxy isomers (in this case the cascade of reactions does not involve methyl transposition).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…7 Later, after optimization work using LAH, 8 NaBH 4 , 9 etc., the regioselective reduction of the resultant imides 10a-c was performed with a large excess of NaBH 4 (6 equiv.) in analogy to our reports for related structures 5 and others 9 to afford α-hydroxy lactams 4a-c in good yields (67%, 75% and 96%, respectively; see Scheme 2). In some cases, to avoid the relatively poor solubility of the starting imides 10 and the laborious work-up encountered during these processes, a small quantity of THF was added as co-solvent.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…7 Later, after optimization work using LAH, 8 NaBH 4 , 9 etc., the regioselective reduction of the resultant imides 10a-c was performed with a large excess of NaBH 4 (6 equiv.) in analogy to our reports for related structures 5 and others 9 to afford α-hydroxy lactams 4a-c in good yields (67%, 75% and 96%, respectively; see Scheme 2). In some cases, to avoid the relatively poor solubility of the starting imides 10 and the laborious work-up encountered during these processes, a small quantity of THF was added as co-solvent.…”
Section: Resultsmentioning
confidence: 89%
“…For this purpose, the α-hydroxy lactam 12 that we described recently 5 was considered. Thus, treatment of 12 in neat TFA in precise amount to the reactant (1.5 mL per 1 mmol of 12) provided the product 15 exclusively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…60 It was shown that the initially formed hydroxyimidazolidinone 32b underwent a peculiar acid-catalyzed reaction in the presence of p-TsOH, involving a methyl group transfer and elimination of water molecule, resulting in the formation of imidazolone 1aa. The synthesis of 1-substituted 1H-imidazol-2(3H)-ones from imidazolidine-2,4-diones (hydantoins) was first described already in 1950.…”
Section: Scheme 38mentioning
confidence: 99%
“…was used, only the direct arylation reaction occurred, leading to 37, probably due to diminished nucleophilicity of the sulfur atom as a result of coordination to the Lewis acid (Scheme 11). [27] In this context, bismuth(III) triflate has been found to promote the formation of cyclic acyliminium ions in remarkably low amounts (1 mol-%), suitable for both inter- and intramolecular reactions. [28] As depicted in Scheme 12, Bi(OTf) 3 -catalyzed intramolecular cyclizations of the acetoxylactams 39, obtained from the imides 38, took place in acetonitrile at room temperature, in an improvement on the results previously obtained for these substrates with TFA.…”
Section: Intramolecular α-Amidoalkylation and Parham Cyclization -Intmentioning
confidence: 99%